Pengembangan Sistem Informasi Keuangan dalam Pengeluaran Anggaran di Dinas Pariwisata dan Budaya Provinsi Jawa Barat - Fanny Ayu Fattimah; Widya Hanifah; Rina Kurniawati; Muthmainnah (KITA Institute, 2023)
From now on, technology and people will become one, like two things that cannot be separated. When two elements are related and can be combined into one system. A current general term that includes the term information system. The purpose of developing the information system itself is to create a product containing useful information. As a government agency implementing the Regional Technology Unit (UPTD), Stimulant is critical to maintaining and operating existing government systems. Of course, data collection also requires accurate, complete and appropriate information systems. However, here we found a problem with the section of the data management information system for artists who are eligible to receive stimulants from the UPTD service. This is due to delays in sending artist data to UPTD. Data were acquired in a descriptive manner using a qualitative approach. As students who are actively engaged in technological development, and as a form of involvement in development, we are well-suited to play a role in serving the communities around us by proposing better systems to the government. The system we have created is in the form of a website where data can be uploaded and easily accessed by administrators of the UPTD service. By applying a waterfall method that creates a container for the artist's data.